White-box testing framework for object-oriented programming: an approach based on message sequence specification and aspect oriented programming - Larrea, Martín (2019)
The quality of software has become one of the most important factor in determining the success of products or enterprises. This paper presents a white-box testing framework for Object-Oriented Programming based on Message Sequence Specification and Aspect Oriented Programming. In the context of an Object-Oriented program, our framework can be used to test the correct order in which the methods of a class are invoked.